Business Strategy Recommendation for Que Rico Hamburguesa Restaurant - Badalamenti, Vorega; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2013)
Food and beverage industry in Indonesia is growing rapidly. Burger is one kind of food growing and popular on the market. Number of restaurants and burger outlets are increasing. They offer a burger at a low price even expensive, but did not consider the quality of the burger itself. By looking at these opportunities, Que Rico Hamburguesa established as the pioneer of unique and healthy burger at affordable prices. As a restaurant that has not been in business long enough, Que Rico Hamburguesa faces some problems and challenges. The emergence of competitors in the area makes the competition within industry really tight, Que Rico Hamburguesa does not have appropriate business model and concept yet to be able to survive and win the competition in this industry. This study methodology using qualitative approach by conducting interview with the owner, observation the business activities, and spreading questionnaires to 150 people of Que Rico HamburguesaÃ¢â‚¬â„¢s customers. All those things are done to obtain information to support this research. The data combined with the external and internal factors are analyzed in order to find the solution of the problems and challenges being faced by Que Rico Restaurant Hamburguesa. This research is focused on the making of business strategy for Que Rico Restaurant Hamburguesa using three business strategies to solve the problems and to prepare development strategy for the future. First is Diamond Strategy, which giving the company direction to achieve their vision, implementation strategy, and increase its brandÃ‚Â awareness. Second is Generic Competitive Strategies that define the concept of Que Rico Hamburguesa Restaurant. Que Rico Hamburguesa should focus on differentiation. The last one is Business Model that can determine the identity of Que Rico Hamburguesa business itself by using nine elements of the business model canvas. Those strategiesis as the solutions must be implement properly and systematically execute. Divided into short term and long term plan with several important aspects that should be considered in order to continue to survive in this industry and develop its business.Ã‚Â Keywords: Fast Food, Business Model, Business Strategy